Analytical and medico‐legal problems linked to the presence of delta‐8‐tetrahydrocannabinol (delta‐8‐THC): Results from urine drug testing in Sweden. Issue 2 (10th November 2021) - Helander, Anders; Johansson, Malin; Andersson, Annika; Villén, Tomas
Abstract: During routine urine drug testing for cannabis use targeting delta‐9‐tetrahydrocannabinol carboxylic acid (delta‐9‐THC‐COOH) at the Karolinska University Laboratory in Sweden, an unknown interfering peak was observed in the liquid‐chromatographic–tandem mass‐spectrometric (LC–MS/MS) confirmative analysis. The peak showed the same exact mass and most abundant fragments as delta‐9‐THC‐COOH but a slightly shorter retention time, thereby not fulfilling all requirements for a positive identification. The analytical results suggested that it was a similar compound, and with access to reference material, it could be identified as the double bond isomer delta‐8‐THC‐COOH. Delta‐8‐THC has recently become popular as a recreational drug, although its legality varies and is sometimes unclear. In Sweden, all THC isomers are classified substances. The slight difference in retention times was sufficient to distinguish the THC‐COOH isomers in the routine LC–MS/MS method, but another LC method allowed better peak separation and individual quantification. At the Karolinska University Laboratory, delta‐8‐THC‐COOH was first observed in April 2020, and the highest incidence was noted in June 2020 when it was present in 5.3% of all THC‐COOH‐positive samples. The incidence later decreased to today only occasional findings. Large differences in the relative presence of the isomers in the urine samples indicated different origin, for example, synthetically produced pure delta‐8‐THC, or mixtures of both THC isomers formed during combustion of cannabidiol (CBD). In conclusion, the appearance of delta‐8‐THC and other isomers on the recreational drug market risks causing analytical and medico‐legal problems, due to confusion with delta‐9‐THC. Abstract : During LC–MS/MS urine drug testing for cannabis use targeting delta‐9‐THC‐COOH, an unknown peak with identical mass and MS fragments but a slightly shorter retention time was first observed in April 2020. The compound was identified as the double bond isomer delta‐8‐THC‐COOH. Delta‐8‐THC has recently become popular as a recreational drug. The incidence peaked in June 2020 (5.3% of THC‐COOH‐positive samples) but has since decreased. The appearance of THC isomers risk causing analytical and medico‐legal problems, due to confusion with delta‐9‐THC.